2016
DOI: 10.1021/acs.inorgchem.6b00972
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxorhenium(V) and Oxotechnetium(V) Complexes That Bind to Amyloid-β Plaques

Abstract: Alzheimer's disease is characterized by the presence of amyloid plaques in the brain. The primary constituents of the plaques are aggregated forms of the amyloid-β (Aβ) peptide. With the goal of preparing technetium-99(m) complexes that bind to Aβ plaques with the potential to be diagnostic imaging agents for Alzheimer's disease, new tetradentate ligands capable of forming neutral and lipophilic complexes with oxotechentium(V) and oxorhenium(V) were prepared. Nonradioactive isotopes of technetium are not avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Therefore, the significant drop in absorbance at 450 nm below pH = 6 (red arrow in Figure b) was mainly due to the precipitation of 1b . The formation of visible aggregates due to precipitation results in spectral deformation. Not only is the absorbance at 450 nm drastically diminished, but the gain in absorbance at 580 nm is attenuated as well, due to fewer absorbing molecules in the illuminated volume (blue arrow).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the significant drop in absorbance at 450 nm below pH = 6 (red arrow in Figure b) was mainly due to the precipitation of 1b . The formation of visible aggregates due to precipitation results in spectral deformation. Not only is the absorbance at 450 nm drastically diminished, but the gain in absorbance at 580 nm is attenuated as well, due to fewer absorbing molecules in the illuminated volume (blue arrow).…”
Section: Resultsmentioning
confidence: 99%
“…[ 99m Tc]122 brain accumulation in rhesus monkeys (M04: 4-year-old, male; F27: 27-year-old, female). [91] ( Figure 29). The affinity of 133 for Aβ 1−42 fibrils was estimated to be K i = 855 nM using a fluorescence competition assay against Thioflavin T. It was also shown that 133 binds to Aβ plaques in human brain tissue using human AD brain sections.…”
Section: M Tc 3+ -Based Coordination Compounds For Spect Visualizatmentioning
confidence: 99%
“…Previous work from our laboratory investigated the potential of the incorporation of an Aβ-targeting styrylpyridyl functional group within the ligand framework . Charge-neutral tetradentate rhenium and technetium complexes featuring pyridyl, amide, and phenol donor atoms were formed where the styrylpyridyl group was directly coordinated to the metal center and the rhenium complexes were able to interact with Aβ plaques present in human brain tissue .…”
Section: Introductionmentioning
confidence: 99%